Sponge-Associated Polychaetes: Not a Random Assemblage - Goren, Liron; Idan, Tal; Shefer, Sigal; Ilan, Micha (Frontiers in Marine Science, 2021)
Polychaetes are among the most common marine organisms, and in many habitats they dominate both in species richness and abundance. They are often found in association with other organisms. Specifically, sponges with their complex three-dimensional internal architecture, are known to host a great diversity of polychaetes. Due to the fact that a large number of sponge-associated polychaete species are known to be common on other substrates, most studies agree that they represent an opportunistic part of the sponge-inhabiting assemblage, without any selection of species tightly associated with sponges. The current study aimed to shed light on polychaetes affinity to sponges. We applied Clarke and Warwick’s taxonomic distinctness indices and test for random assembly, to a dataset compiled of 13 publications that provided polychaete species lists from massive-sponges across the Mediterranean Sea, and compared them with benthic-polychaete species lists from all of the Mediterranean and its zoogeographical regions. These indices are considered to be independent of sampling efforts and setting, and can be applied on presence/absence data, making it possible to compare data from multiple studies. We further compared the trophic structure of sponge-associated polychaetes between the Mediterranean’s zoogeographical regions. Our results show that the trophic structure of the sponge-associated polychaete community, was found to be stable across the entire Mediterranean Sea. Moreover, randomization tests showed that at almost all observational scales (e.g., study, region, Mediterranean) the phylogenetic diversity is not assembled at random, and that sponge-associated polychaete communities are composed of taxonomically related species. These results support the statement that polychaete assemblages inhabiting sponges are not a transient facultative assembly of species, but rather stable, diverse and specialized communities which are well adapted for life in this habitat.